Water-gas shift catalyst, preparation method and application thereof, and water-gas shift reaction method
By developing water vapor transformation catalysts containing alumina, activated iron and additive elements, the problems of poor heat resistance and low hydrogen production rate of existing catalysts are solved, and efficient CO conversion and hydrogen production are achieved without chromium pollution.
Patent Information
- Application Number
- CN202311283716.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The existing water vapor conversion catalysts have problems such as poor heat resistance and low hydrogen production rate, and are seriously polluted by chromium and have high costs.
A water vapor transformation catalyst including alumina, active elements (divalent and trivalent iron) and additive elements (Co, Ni, Cr, Cu and Ce) was developed. The Fe2+/Fe3+ atomic ratio on the catalyst surface was determined by XPS to synthesize the catalyst using a one-step self-assembly method to form a uniform mesoporous structure.
The catalyst has a high CO conversion rate and hydrogen production rate under high airspeed conditions, good heat resistance, high activity retention rate after high temperature treatment, and no chromium pollution, and the preparation process is simple.
Smart Images

Figure CN119746864A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water vapor shift, and in particular to a water vapor shift catalyst and a preparation method and application thereof, and a water vapor shift reaction method. Background Art
[0002] At present, steam reforming of methane (SRM) is a mature industrial hydrogen production technology. In order to increase the hydrogen yield, a water-gas shift reaction is required after the reforming process to react the excess CO and further increase the H2 content in the atmosphere, thereby increasing the hydrogen yield. In addition, in recent years, the water-gas shift reaction has also had important applications in the field of new energy vehicles. The electrode material of the fuel cell is mainly composed of Pt, which is easily deactivated in the presence of carbon monoxide. Therefore, the water-gas shift reactor is placed before the fuel cell to convert carbon monoxide into hydrogen and CO2 gas. It can be seen that the water-gas shift reaction (WGS) plays an important industrial role in regulating and increasing the H2 concentration.
[0003] Commercial iron oxide catalysts with chromium oxide as a structural additive have been used for more than 60 years. In addition to being a structural additive to prevent the sintering of iron oxide crystals, Cr2O3 / CrO3 can also improve the inherent catalytic activity of Fe2O3. Although chromium oxide has been proven to be a good additive, hexavalent chromium is a heavy metal that is toxic to humans, organisms or cells, and is also a serious environmental pollutant. The water solubility of hexavalent chromium causes it to leach from the catalyst through condensed steam or cold water. The hexavalent chromium (Cr) of fresh and discarded commercial high-temperature conversion Fe-Cr catalysts 6+ ), the processing cost is very high.
[0004] CN107649142A discloses the use of Mn, Mg, and Cr as additives to improve the high-temperature stability of Fe-based catalysts, but still contains a low content of Cr; CN103272600A discloses a hydrothermally synthesized supported copper-iron catalyst, but its hydrothermal reaction time is long and the process is cumbersome; CN104014345A discloses the synthesis of Cu / CeO2 catalysts by deposition precipitation method, but the deposition consumes a lot of heat and the catalyst preparation cost is high.
[0005] The main problems faced by the water-gas shift reaction surface in the existing technology include serious methanogenic side reactions, low time-space yield, high catalyst cost, serious chromium pollution, etc. Therefore, how to develop chromium-free, highly selective, and simple preparation process catalysts under the premise of ensuring hydrothermal stability is the difficulty and direction of realizing the industrial application of green shift catalysts. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems of poor heat resistance and low hydrogen production rate of water vapor shift catalysts in the prior art, and to provide a water vapor shift catalyst and its preparation method and application, and a method for water vapor shift reaction. The catalyst has high thermal stability and resistance to hydrothermal and sintering.
[0007] In order to achieve the above-mentioned purpose, the present invention provides a water gas shift catalyst on the one hand, which includes alumina, an active element and an auxiliary element; the auxiliary element is selected from at least one of Co, Ni, Cr, Cu and Ce; the active element includes divalent iron and trivalent iron, and the atomic ratio of divalent iron to trivalent iron on the surface of the catalyst measured by XPS is not less than 0.3.
[0008] Preferably, the total pore volume of the catalyst is 0.01-0.6 mL / g, preferably 0.3-0.5 mL / g;
[0009] Preferably, the average pore size of the catalyst is 5-15 nm, preferably 8-12 nm.
[0010] A second aspect of the present invention provides a method for preparing a water gas shift catalyst, comprising the following steps:
[0011] (1) mixing aluminum isopropoxide, a first template, and an acid in the presence of a first dispersant to obtain a first solution;
[0012] (2) in the presence of a second dispersant, mixing a divalent iron source, a trivalent iron source, a soluble compound containing an auxiliary element, and a second template to obtain a second solution; wherein the molar ratio of the divalent iron source to the trivalent iron source is 1-3:1, calculated as iron element; and the auxiliary element is selected from at least one of Co, Ni, Cr, Cu, and Ce;
[0013] (3) mixing the first solution and the second solution under stirring to obtain a gel;
[0014] (4) Drying, washing and calcining the gel.
[0015] Preferably, the drying temperature in step (4) is not less than 90°C, preferably 100-150°C, and more preferably 110-130°C; the drying time is 12-84h, preferably 24-48h.
[0016] The third aspect of the present invention provides the use of the above-mentioned water vapor shift catalyst or the water vapor shift catalyst prepared by the above-mentioned preparation method in a water vapor shift reaction.
[0017] A fourth aspect of the present invention provides a method for a water gas shift reaction, comprising: contacting a raw gas containing CO, water vapor and a catalyst under water gas shift reaction conditions to perform a water gas shift reaction;
[0018] Wherein, the catalyst is the water gas shift catalyst of the first aspect or the water gas shift catalyst prepared by the preparation method provided by the second aspect.
[0019] The water gas shift catalyst provided by the present invention comprises aluminum oxide, an active element and an auxiliary element, and the atomic ratio of divalent iron to trivalent iron on the catalyst surface is not less than 0.3. The inventors of the present invention have found in their research that Fe 2+ / Fe 3+ The ratio is the key to the activity and stability of the catalyst. The catalyst with the above composition is applied to the water vapor change reaction, is suitable for low water vapor ratio conditions, has a high CO conversion rate and a high hydrogen production rate under high space velocity conditions, has good heat resistance and activity retention rate after high temperature treatment. Preferably, the catalyst has a large number of uniform mesoporous structures, a large total pore volume, and a small average pore size, which is conducive to stabilizing the catalyst structure, improving the thermal stability of the catalyst, and improving the catalytic activity of the catalyst and the hydrogen production rate.
[0020] The preparation method of the water gas shift catalyst provided by the present invention adopts a one-step self-assembly method to synthesize the catalyst, and almost no wastewater is generated during the preparation process, and the production process is simple. By introducing an auxiliary agent to cooperate with a divalent iron source and a trivalent iron source, the surface of the prepared catalyst has a suitable Fe 2+ / Fe 3+ In a preferred embodiment, by introducing aluminum isopropoxide and controlling the rapid drying of the gel to shorten the growth time, a uniform mesoporous structure can be formed with a large total pore volume and a small average pore size, and the obtained catalyst has good heat resistance and high activity retention after high temperature treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a TEM image of catalyst A1 prepared in Example 1 of the present invention;
[0022] Figure 2 It is the XPS curve and Fe 2p peak separation result of catalyst A1 prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0023] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0024] A first aspect of the present invention provides a water gas shift catalyst, which includes alumina, an active element and an auxiliary element; the auxiliary element is selected from at least one of Co, Ni, Cr, Cu and Ce; the active element includes divalent iron and trivalent iron, and the atomic ratio of divalent iron to trivalent iron on the surface of the catalyst measured by XPS is not less than 0.3.
[0025] The inventors of the present invention have found in their research that Fe 2+ / Fe 3+ The ratio is the key to the activity and stability of the catalyst. The catalyst with the above composition is used in the water vapor change reaction, is suitable for low water vapor ratio conditions, has a high CO conversion rate and a high hydrogen production rate under high space velocity conditions, has good heat resistance and activity retention rate after high temperature treatment. The iron element in the iron-based catalyst in the prior art is basically Fe 3+ .
[0026] According to some preferred embodiments of the present invention, the atomic ratio of ferrous iron to ferric iron on the catalyst surface measured by XPS is 0.4-1. For example, the atomic ratio of ferrous iron to ferric iron on the catalyst surface measured by XPS can be 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, or other specific point values or any range between the two. Preferably, the atomic ratio of ferrous iron to ferric iron on the catalyst surface measured by XPS is 0.5-0.8. The atomic ratio of ferrous iron to ferric iron on the catalyst surface is within the above preferred range, which is conducive to further improving the reaction activity and stability, and has good heat resistance activity.
[0027] In the present invention, in-situ XPS characterization is performed on an ESCALAB 250 X-ray photoelectron spectrometer produced by Thermo Fisher-VG, the excitation source is AlKαX-ray with a monochromatic power of 150W, and the charging effect comes from the correction of the Al 2p peak (74.7eV) of the carrier Al2O3 or the Si 2p peak (103.6eV) of SiO2. The reduction conditions are a heating rate of 5°C / min, pure H2 gas, a reaction pressure of 0.12MPa, and reduction for 3h after heating to the target temperature.
[0028] In some preferred embodiments of the present invention, the molar ratio of the active element to the auxiliary element is 1-50: 1, preferably 5-20: 1. In the present invention, the auxiliary element in the catalyst helps to stabilize the divalent iron on the catalyst surface, and on the other hand, the synergistic effect of the auxiliary element with the divalent iron and the trivalent iron is conducive to providing higher activity in the water gas shift reaction.
[0029] According to some preferred embodiments of the present invention, the auxiliary element is selected from at least two of Co, Ni, Cr, Cu and Ce. In the above preferred case, it is beneficial to improve the water gas shift catalytic activity of the catalyst. In order to further improve the activity of the catalyst at low temperatures, preferably, the auxiliary element includes Cu, and optionally Ni and / or Cr. The above preferred composition is conducive to the water gas shift reaction under relatively mild reaction conditions and has higher activity.
[0030] In a further preferred embodiment, in the auxiliary element, the ratio of the molar amount of Cu to the total molar amount of Ni and / or Cr is 0.05-1:1, preferably 0.1-0.3:1.
[0031] In the present invention, the active elements and auxiliary elements exist in the form of oxides.
[0032] According to some preferred embodiments of the present invention, based on the mass of the catalyst, the content of aluminum oxide is 20-80wt%, preferably 40-70wt%; the content of active elements in terms of oxide is 20-80wt%, preferably 30-60wt%; the content of auxiliary elements in terms of oxide is 0.1-10wt%, preferably 1-8wt%. In the present invention, the content of iron element is calculated as ferric oxide.
[0033] In the present invention, the composition of the catalyst is determined by an X-ray fluorescence spectrometry (XRF) method.
[0034] According to some preferred embodiments of the present invention, the total pore volume of the catalyst is 0.01-0.6 mL / g, preferably 0.2-0.5 mL / g.
[0035] Preferably, the catalyst provided by the present invention has a smaller average pore size, and the pore distribution is mainly mesoporous structure, which is beneficial to stabilizing the catalyst structure, improving the thermal stability of the catalyst, and improving the catalytic activity of the catalyst and the hydrogen production rate.
[0036] Preferably, the average pore size of the catalyst is 5-15 nm, preferably 8-12 nm, for example, it can be 8 nm, 8.5 nm, 9 nm, 9.5 nm, 10 nm, 10.5 nm, 11 nm, 11.5 nm, 12 nm and other typical but non-limiting values or ranges therebetween.
[0037] The average pore size of the catalyst was analyzed by low-temperature N2 constant temperature adsorption-desorption and conventional BET calculation. Before analysis, the sample was dried at 120℃ for 2h and then evacuated under vacuum at 300℃. The adsorption medium was high-purity nitrogen. The adsorption / desorption experiment was carried out under liquid nitrogen cooling conditions (-196℃).
[0038] A second aspect of the present invention provides a method for preparing a water gas shift catalyst, comprising the following steps:
[0039] (1) mixing aluminum isopropoxide, a first template, and an acid in the presence of a first dispersant to obtain a first solution;
[0040] (2) in the presence of a second dispersant, mixing a divalent iron source, a trivalent iron source, a soluble compound containing an auxiliary element, and a second template to obtain a second solution; wherein the molar ratio of the divalent iron source to the trivalent iron source is 1-3:1, calculated as iron element; and the auxiliary element is selected from at least one of Co, Ni, Cr, Cu, and Ce;
[0041] (3) mixing the first solution and the second solution under stirring to obtain a gel;
[0042] (4) Drying, washing and calcining the gel.
[0043] According to the present invention, a one-step self-assembly method is used to synthesize the catalyst, by introducing a divalent iron source and a trivalent iron source, introducing an appropriate amount of divalent iron and trivalent iron into the catalyst, and under the synergistic effect of the additive, the surface of the prepared catalyst has a suitable Fe 2+ / Fe 3+ Preferably, the molar ratio of the divalent iron source to the trivalent iron source is 1.5-2.5:1, calculated as the iron element.
[0044] According to some preferred embodiments of the present invention, the first template and the second template are independently selected from at least one of hexadecyltrimethylammonium bromide (CTAB), polyoxyethylene / polyoxypropylene / polyoxyethylene amphiphilic block copolymer (F127), polyethylene oxide-polypropylene oxide-polyoxyethylene triblock copolymer (P123), polyoxyethylene polyoxypropylene clamp polyether (F108), polyethylene glycol (PEG) and polyoxyethylene ether. The selection of the first template and the second template can be the same or different, and preferably, the first template is the same as the second template.
[0045] According to some preferred embodiments of the present invention, in step (1), the mass ratio of the first template to aluminum isopropoxide is 0.1-1:1, preferably 0.2-0.8:1.
[0046] According to some preferred embodiments of the present invention, the mass ratio of the aluminum isopropoxide to the acid is 0.1-10: 1, preferably 1-5: 1. In the above preferred case, the formation of mesoporous alumina is facilitated.
[0047] Preferably, the acid is citric acid and / or nitric acid.
[0048] According to some preferred embodiments of the present invention, the first dispersant is used in an amount such that the concentration of aluminum isopropoxide in the first solution is 0.05-1 g / mL, preferably 0.1-0.5 g / mL.
[0049] According to some preferred embodiments of the present invention, the ratio of the mass of the second template to the mass of the first template is 0.1-1:1.
[0050] According to some preferred embodiments of the present invention, the auxiliary element is selected from at least two of Co, Ni, Cr, Cu and Ce. In the above preferred cases, it is beneficial to improve the water gas shift catalytic activity of the catalyst. In order to further improve the activity of the catalyst at low temperatures; preferably, the auxiliary element includes Cu, and optionally Ni and / or Cr. By adopting the above preferred composition, it is beneficial for the water gas shift reaction to proceed under relatively mild reaction conditions and has higher activity.
[0051] According to some preferred embodiments of the present invention, in the auxiliary element, the ratio of the molar amount of Cu to the total molar amount of Ni and / or Cr is 0.05-1:1, preferably 0.1-0.3:1.
[0052] According to some preferred embodiments of the present invention, the ratio of the total molar amount of the divalent iron source and the trivalent iron source to the molar amount of the soluble compound containing the auxiliary element, calculated as metal elements, is 1-50: 1, preferably 5-20: 1. In the above preferred case, it is beneficial to form a suitable ratio of divalent iron and trivalent iron on the catalyst surface, and the synergistic effect of the auxiliary element with divalent iron and trivalent iron is beneficial to the activity and stability in the water gas shift reaction.
[0053] The present invention has a wide range of selection for the specific types of the ferrous iron source, ferric iron source and soluble compound containing auxiliary elements. As long as the corresponding metal source can be provided, those skilled in the art can make the selection according to the actual situation.
[0054] According to some preferred embodiments of the present invention, the ferrous iron source, the ferric iron source and the soluble compound containing the auxiliary element are each independently selected from inorganic salts and / or organic salts of metals, preferably at least one of nitrates, sulfates, halides, acetates and formates. For example, the ferrous iron source may be ferrous chloride, and the ferric iron source may be ferric nitrate.
[0055] According to some preferred embodiments of the present invention, the stirring time in step (3) is 1-10 h, preferably 3-6 h.
[0056] According to some preferred embodiments of the present invention, the amounts of the first solution and the second solution are such that, based on the total amount of the prepared catalyst, the content of aluminum oxide is 20-80wt%, preferably 40-70wt%; the content of active elements calculated as oxides is 20-80wt%, preferably 30-60wt%; the content of auxiliary elements calculated as oxides is 0.1-10wt%, preferably 1-8wt%.
[0057] According to some preferred embodiments of the present invention, the drying temperature in step (4) is not less than 90°C, preferably 100-150°C, and more preferably 110-130°C; the drying time is 12-84h, and preferably 24-72h. The above preferred drying conditions are beneficial to further improve the heat resistance activity of the catalyst. The reason may be that under the above conditions, the gel dries quickly, grows fast and takes a short time, so that a uniform mesoporous structure is formed in the catalyst.
[0058] According to some preferred embodiments of the present invention, the calcination conditions include: a calcination temperature of 300-500° C., preferably 350-450° C.; and a calcination time of 2-8 h, preferably 4-6 h.
[0059] Preferably, the preparation method further comprises: molding and screening the product obtained by calcination; the molding method can be selected according to the actual application needs and is well known to those skilled in the art, for example, it can be tablet molding.
[0060] The third aspect of the present invention provides the use of the above-mentioned water vapor shift catalyst or the water vapor shift catalyst prepared by the above-mentioned preparation method in a water vapor shift reaction.
[0061] A fourth aspect of the present invention provides a method for a water gas shift reaction, comprising: contacting a raw gas containing CO, water vapor and a catalyst under water gas shift reaction conditions to perform a water gas shift reaction;
[0062] Wherein, the catalyst is the water vapor shift catalyst mentioned above or the water vapor shift catalyst prepared by the above preparation method.
[0063] In the present invention, the water gas shift reaction can have a higher CO conversion rate and a higher hydrogen production rate under higher space velocity conditions.
[0064] According to some preferred embodiments of the present invention, the water gas shift reaction conditions include: reaction temperature of 300-500°C, preferably 350-450°C; reaction pressure of 0.1-5MPa, preferably 1-2MPa; mass space velocity of feed gas of 5000-20000h -1 , preferably 10000-18000h -1; The water-to-carbon ratio is 2.4-4, preferably 2.8-3.5.
[0065] Preferably, the water gas shift reaction is carried out in a fixed bed reactor.
[0066] According to some preferred embodiments of the present invention, the method further comprises: before the contacting, subjecting the catalyst to a reduction pretreatment in a reducing atmosphere containing H2 and / or CO.
[0067] Preferably, the reduction pretreatment conditions include: temperature of 200-600°C; time of 1-12h; pressure of 0.1-1MPa, and air velocity of 500-20000h -1 More preferably, the temperature is 300-400°C; the time is 2-6 hours; the pressure is 0.1-1 MPa, and the air velocity is 5000-20000. -1 .
[0068] Preferably, the reducing atmosphere may also contain water vapor and / or carbon dioxide. Preferably, the total volume content of H2 and / or CO in the reducing atmosphere is not less than 30%, preferably 35-65%.
[0069] The present invention will be described in detail below through examples.
[0070] In the following examples and comparative examples, unless otherwise specified, the raw materials used were commercially available.
[0071] Catalyst mesopore volume and average pore size test: The pore volume of the catalyst was analyzed by low-temperature N2 constant temperature adsorption-desorption and conventional BET calculation processing. Before analysis, the sample was dried at 120℃ for 2h and then evacuated under vacuum and 300℃. The adsorption medium was high-purity nitrogen. The adsorption / desorption experiment was carried out under liquid nitrogen cooling conditions (-196℃).
[0072] The composition of the catalyst was determined by XRF method.
[0073] The valence state of the iron element on the catalyst surface and the content of divalent iron and trivalent iron were determined by X-ray photoelectron spectroscopy (XPS) on an ESCALAB 250 X-ray photoelectron spectrometer produced by Thermo Fisher-VG. The excitation source was AlKαX-ray with a monochromatic power of 150W, and the charging effect was corrected by the Al 2p peak (74.7eV) of the carrier Al2O3 or the Si2p peak (103.6eV) of SiO2. The reduction conditions were a heating rate of 5°C / min, pure H2 gas, a reaction pressure of 0.12MPa, and reduction for 3h after heating to the target temperature.
[0074] Example 1
[0075] Dissolve 20 g of P123 in 300 mL of anhydrous ethanol and stir vigorously to dissolve. Add 30 g of aluminum isopropoxide and 33.6 g of 67 wt% nitric acid solution to the above solution and stir for 1 hour to obtain a first solution. Add 10 g of P123, 6.37 g of ferric nitrate nonahydrate, 6.27 g of ferrous chloride tetrahydrate, 0.124 g of copper nitrate trihydrate, and 0.785 g of nickel nitrate hexahydrate to 150 mL of anhydrous ethanol and stir for 1 hour to obtain a second solution.
[0076] The second solution was mixed with the first solution, stirred for 8 hours to obtain a gel, and stored in a 120°C thermostat for 48 hours to evaporate the solvent. The catalyst A1 was then calcined at 400°C for 5 hours. The catalyst A1 was pressed into tablets at 15 MPa, crushed, and screened to 40-60 mesh for reaction evaluation.
[0077] The morphology of the catalyst was characterized by TEM. Figure 1 As shown in Figure 2, the active metal in the catalyst maintains a small grain size. The elemental composition of the catalyst surface was tested by XPS. The XPS test curve and Fe 2p peak results are shown in Figure 2. Figure 2 As shown, it can be seen that the catalyst surface contains divalent iron and trivalent iron.
[0078] The physicochemical characteristics of the tested catalysts are listed in Table 1 and Table 1 cont.
[0079] Example 2
[0080] Dissolve 10 g of P123 in 200 mL of anhydrous ethanol and stir vigorously to dissolve. Add 17.8 g of aluminum isopropoxide and 22.4 g of 67 wt% nitric acid solution to the above solution and stir for 1 hour to obtain a first solution. Add 10 g of P123, 4.13 g of ferric nitrate nonahydrate, 4.07 g of ferrous chloride tetrahydrate, 0.08 g of cupric nitrate trihydrate, and 1.23 g of chromium nitrate nonahydrate to 150 mL of anhydrous ethanol and stir for 1 hour to obtain a second solution.
[0081] The second solution was mixed with the first solution, stirred for 5 hours to obtain a gel, and stored in a 120°C thermostat for 48 hours to evaporate the solvent. The catalyst A2 was then calcined at 400°C for 5 hours. The catalyst A2 was pressed into tablets at 15 MPa, crushed, and screened to 40-60 mesh for reaction evaluation.
[0082] The morphology of the catalyst and Figure 1 Similarly, by testing the elemental composition of the catalyst surface through XPS, it can be seen that the catalyst surface contains divalent iron and trivalent iron.
[0083] The physicochemical characteristics of the tested catalysts are listed in Table 1 and Table 1 cont.
[0084] Example 3
[0085] Dissolve 10 g of P123 in 100 mL of anhydrous ethanol and stir vigorously to dissolve. Add 10 g of aluminum isopropoxide and 11.2 g of 67 wt% nitric acid solution to the above solution and stir for 1 hour to obtain a first solution. Add 5 g of P123, 2.03 g of ferric nitrate nonahydrate, 2 g of ferrous chloride tetrahydrate, and 0.08 g of copper nitrate trihydrate into 50 mL of anhydrous ethanol and stir for 1 hour to obtain a second solution.
[0086] The second solution was mixed with the first solution, stirred for 5 hours to obtain a gel, and stored in a 120°C thermostat for 48 hours to evaporate the solvent. The catalyst A3 was then calcined at 400°C for 5 hours. The catalyst A3 was pressed into tablets at 15 MPa, crushed, and screened to 40-60 mesh for reaction evaluation.
[0087] The physicochemical characteristics of the tested catalysts are listed in Table 1 and Table 1 cont.
[0088] Example 4
[0089] The method of Example 1 was followed, except that in the second solution, the mass of ferric nitrate nonahydrate was 12 g, and the mass of ferrous chloride tetrahydrate was 5.91 g. Catalyst A4 was obtained. The catalyst was pressed into tablets at 15 MPa, crushed, and screened to 40-60 mesh for reaction evaluation.
[0090] The physicochemical characteristics of the tested catalysts are listed in Table 1 and Table 1 cont.
[0091] Example 5
[0092] Catalyst A5 was obtained by the method of Example 1, except that in the second solution, the mass of copper nitrate trihydrate was 0.76 g and the mass of nickel nitrate hexahydrate was 0.688 g. The catalyst was pressed into tablets at 15 MPa, crushed, and screened to 40-60 mesh for reaction evaluation.
[0093] The physicochemical characteristics of the tested catalysts are listed in Table 1 and Table 1 cont.
[0094] Example 6
[0095] The method of Example 1 was followed, except that the gel was stored in a 40°C thermostat for 120 hours to evaporate the solvent, and then calcined at 400°C for 5 hours to obtain catalyst A6. The pellets were pressed at 15 MPa, crushed, and screened to 40-60 mesh for reaction evaluation.
[0096] The physicochemical characteristics of the tested catalysts are listed in Table 1 and Table 1 cont.
[0097] Comparative Example 1
[0098] Dissolve 20g of ferric nitrate nine hydrate, 0.72g of nickel nitrate hexahydrate, 0.60g of copper nitrate trihydrate, and 0.5g of P123 (5800) in 100mL of ethanol and 50mL of deionized water to obtain solution A. Dissolve 30g of ammonia water (mass fraction 25% to 28%) in 50mL of ethanol and 20mL of deionized water to obtain solution B. Add solution B to solution A at 5mL / min through a peristaltic pump, stir for 4h, store in a 120℃ thermostat for 48h, and wait for the solvent to evaporate. Roast at 400℃ for 5h to obtain catalyst DA1. Press tablets at 15MPa, crush, and screen 40-60 mesh for reaction evaluation.
[0099] The elemental composition of the catalyst surface was tested by XPS, and the catalyst surface only contained trivalent iron. The physicochemical characteristics of the tested catalyst are listed in Table 1 and Table 1.
[0100] Comparative Example 2
[0101] Dissolve 10g of P123 in 200mL of anhydrous ethanol and stir vigorously to dissolve. Add 22.4g of 67wt% nitric acid solution, 12.4g of iron nitrate nonahydrate, 0.1g of copper nitrate trihydrate, and 1.1g of chromium nitrate nonahydrate to the above solution and stir for 5h to mix evenly. Store in a 120℃ thermostat for 48h until the solvent evaporates. Roast at 400℃ for 5h to obtain catalyst DA2. Press tablets at 15MPa, crush, and screen 40-60 mesh for reaction evaluation.
[0102] The elemental composition of the catalyst surface was tested by XPS, and the catalyst surface only contained trivalent iron. The physicochemical characteristics of the tested catalyst are listed in Table 1 and Table 1.
[0103] Comparative Example 3
[0104] Dissolve 20g of ferric nitrate 9hydrate, 54.12g of aluminum nitrate 9hydrate, 0.60g of copper nitrate trihydrate, and 0.5g of P123 (5800) in 100mL of ethanol and 50mL of deionized water to obtain solution A. Dissolve 30g of ammonia water (mass fraction 25% to 28%) in 50mL of ethanol and 20mL of deionized water to obtain solution B. Add solution B to solution A at 5mL / min through a peristaltic pump, stir for 4h, store in a 120℃ thermostat for 48h, and wait for the solvent to evaporate. Roast at 400℃ for 5h to obtain catalyst DA3. Press tablets at 15MPa, crush, and screen 40-60 mesh for reaction evaluation.
[0105] The elemental composition of the catalyst surface was tested by XPS, and the catalyst surface only contained trivalent iron. The physicochemical characteristics of the tested catalyst are listed in Table 1 and Table 1.
[0106] Table 1
[0107]
[0108] Table 1
[0109]
[0110] Test Case
[0111] The following test examples are used to illustrate the performance of the catalyst of the present invention in catalyzing the water gas shift reaction.
[0112] (1) The catalysts prepared in the examples and comparative examples were pretreated at 400°C for 2 h before evaluation. The pretreatment was carried out under normal pressure and dry gas atmosphere. The composition of the dry gas atmosphere was as follows (volume content): CO / CO2 / H2 / N2 = 24.7% / 8.3% / 49.5% / 17.5%, and the dry gas space velocity was 20000 h -1 , water-to-carbon ratio 3.5.
[0113] Weigh 0.5 g of the pretreated catalyst and load it into a reaction tube with an inner diameter of 8 mm at a dry gas space velocity of 16000 h -1 , water-carbon ratio of 2.4, reaction at normal pressure and 400°C for 2h, product composition analysis by chromatography, calculation of hydrogen production rate, and evaluation results are shown in Table 2.
[0114] in,
[0115]
[0116]
[0117] In the above formula, F CO(进) Refers to the CO flow rate at the reactor inlet, F CO(出) refers to the CO flow rate at the reactor outlet (mL / min), F CH4(进) refers to the CH4 flow rate at the reactor inlet (mL / min), F CH4(出) refers to the CH4 flow rate at the reactor outlet (mL / min), F H2(进) refers to the H2 flow rate at the reactor inlet (mL / min), F H2(出) refers to the H2 flow rate at the reactor outlet (mL / min), V m is the molar volume of the gas (L / mol), M cat is the mass of the loaded catalyst (g).
[0118] (2) The catalysts prepared in the above examples and comparative examples were tested for heat resistance activity.
[0119] The conditions for the heat-resistance activity test are: the atmosphere and space velocity are consistent with the conditions of the water vapor shift reaction, maintained at 530°C for 6 hours, then cooled to 400°C for 4 hours, and the CO conversion rate is tested as the heat-resistance activity;
[0120] Then the activity retention rate after heat resistance was calculated by the following formula, and the results are shown in Table 2.
[0121] The initial activity is the CO conversion rate measured under the conditions of test example (1).
[0122] Table 2
[0123]
[0124] Combining the results of Table 1, Table 1 and Table 2, it can be seen that compared with the comparative example, the catalyst surface of the catalyst prepared in the embodiment of the present invention has a suitable Fe 2+ / Fe 3+ The ratio is suitable for low water-gas ratio conditions. It has a high CO conversion rate and a high hydrogen production rate under high space velocity conditions. It has good heat resistance and activity retention after high temperature treatment. By controlling the gel drying temperature, the catalyst obtained has a large total pore volume and a small average pore size, which is beneficial to stabilizing the catalyst structure and improving the thermal stability of the catalyst, as well as improving the catalytic activity of the catalyst and the hydrogen production rate.
[0125] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A water gas shift catalyst, characterized in that: The catalyst includes alumina, active elements and auxiliary elements; the auxiliary elements are selected from at least one of Co, Ni, Cr, Cu and Ce; the active elements include divalent iron and trivalent iron, and the atomic ratio of divalent iron to trivalent iron on the surface of the catalyst measured by XPS is not less than 0.
3.
2. The catalyst according to claim 1, wherein The atomic ratio of divalent iron to trivalent iron on the catalyst surface measured by XPS is 0.4-1, preferably 0.5-0.
8.
3. The catalyst according to claim 1 or 2, wherein The additive elements include Cu, and optionally Ni and / or Cr; Preferably, in the auxiliary element, the ratio of the molar amount of Cu to the total molar amount of Ni and / or Cr is 0.1-1.
4. The catalyst according to any one of claims 1 to 3, wherein Based on the mass of the catalyst, the content of aluminum oxide is 20-80wt%, preferably 40-70wt%; the content of active elements calculated as oxide is 20-80wt%, preferably 30-60wt%; the content of auxiliary elements calculated as oxide is 0.1-10wt%, preferably 1-8wt%; Preferably, the molar ratio of the active element to the auxiliary element is 1-50:1, preferably 5-20:
1.
5. The catalyst according to any one of claims 1 to 4, wherein The total pore volume of the catalyst is 0.01-0.6 mL / g, preferably 0.3-0.5 mL / g; Preferably, the average pore size of the catalyst is 5-15 nm, preferably 8-12 nm.
6. A method for preparing a water gas shift catalyst, comprising the following steps: (1) mixing aluminum isopropoxide, a first template, and an acid in the presence of a first dispersant to obtain a first solution; (2) in the presence of a second dispersant, mixing a divalent iron source, a trivalent iron source, a soluble compound containing an auxiliary element, and a second template to obtain a second solution; wherein the molar ratio of the divalent iron source to the trivalent iron source is 1-3:1, calculated as iron element; and the auxiliary element is selected from at least one of Co, Ni, Cr, Cu, and Ce; (3) mixing the first solution and the second solution under stirring to obtain a gel; (4) Drying and calcining the gel.
7. The preparation method according to claim 6, wherein: The first template and the second template are each independently selected from at least one of hexadecyltrimethylammonium bromide, polyoxyethylene / polyoxypropylene / polyoxyethylene amphiphilic block copolymers, polyethylene oxide-polyoxypropylene oxide-polyoxyethylene triblock copolymers, polyoxyethylene polyoxypropylene clamp polyethers, polyethylene glycol, and polyoxyethylene ethers; Preferably, in step (1), the mass ratio of the first template to aluminum isopropoxide is 0.1-1:1, preferably 0.2-0.8:1; Preferably, the mass ratio of the aluminum isopropoxide to the acid is 0.1-10:1, preferably 1-5:1; Preferably, the acid is citric acid and / or nitric acid; Preferably, the first dispersant is used in an amount such that the concentration of aluminum isopropoxide in the first solution is 0.05-1 g / mL, preferably 0.1-0.5 g / mL.
8. The preparation method according to claim 6 or 7, wherein: Calculated on the basis of elemental iron, the molar ratio of the ferrous iron source to the ferric iron source is 1.5-2.5:1; Preferably, the ratio of the mass of the second template to the mass of the first template is 0.1-1:1; Preferably, the additive element comprises Cu, and optionally Ni and / or Cr; Preferably, in the auxiliary element, the ratio of the molar amount of Cu to the total molar amount of Ni and / or Cr is 0.05-1; Preferably, the ratio of the total molar amount of the divalent iron source and the trivalent iron source to the molar amount of the soluble compound containing the auxiliary element is 1-50:1, preferably 1-5:1, calculated as metal elements; Preferably, the ferrous iron source, the ferric iron source and the soluble compound containing the auxiliary element are each independently selected from inorganic and / or organic salts of metals, preferably at least one of nitrates, sulfates, halides, acetates and formates.
9. The preparation method according to any one of claims 6 to 8, wherein: The stirring time in step (3) is 1-10 h, preferably 3-6 h; Preferably, the amounts of the first solution and the second solution are such that, based on the total amount of the prepared catalyst, the content of aluminum oxide is 20-80wt%, preferably 40-70wt%; the content of active elements calculated as oxide is 20-80wt%, preferably 30-60wt%; the content of auxiliary elements calculated as oxide is 0.1-10wt%, preferably 1-8wt%.
10. The preparation method according to any one of claims 6 to 9, wherein: The drying temperature in step (4) is not less than 90°C, preferably 100-150°C, and more preferably 110-130°C; the drying time is 12-84h, preferably 24-72h; Preferably, the calcination conditions include: a calcination temperature of 300-500° C. and a calcination time of 2-8 h.
11. Use of the water gas shift catalyst according to any one of claims 1 to 5 or the water gas shift catalyst prepared by the preparation method according to any one of claims 6 to 10 in a water gas shift reaction.
12. A method for water gas shift reaction, characterized in that: include: Under the conditions of water-gas shift reaction, raw gas containing CO, water vapor and catalyst are contacted to perform water-gas shift reaction; Wherein, the catalyst is the water gas shift catalyst according to any one of claims 1 to 5 or the water gas shift catalyst prepared by the preparation method according to any one of claims 6 to 10; Preferably, the water gas shift reaction conditions include: reaction temperature of 300-500°C, preferably 350-450°C; reaction pressure of 0.1-5MPa, preferably 1-2MPa; mass space velocity of feed gas of 5000-20000h -1 , preferably 10000-18000h -1 ; The water-to-carbon ratio is 2.4-4, preferably 2.8-3.5.
Citation Information
Patent Citations
Supported copper-iron water coal gas shift catalyst and preparation method thereof
CN103272600A
CuO-CeO2 catalyst for water gas conversion reaction and preparation method thereof
CN104014345A
Low-density iron chromium series CO transformation catalyst
CN107649142A
Preparation method capable of increasing sulfur tolerance of middle temperature iron-chromium shift catalyst using high-purity nano molybdenum trioxide
CN101491763A
Catalyst for diesel desulfurization, preparation method and application
CN103331161A